Nationalistic historiography or patriotic history? A Look at the discourses of Chronicles from the second Chimurenga: a Sunday Mail Column. - Magorimbo, Blessing (Midlands State University, 2017)
The study set out to explore the discourses in the column Chronicles from the Second Chimurenga in The Sunday Mail .The intention was to find out if it is nationalistic historiography or patriotic history or both histories being propagated on the Column Chronicles from the Second Chimurenga .The theoretical framework of the study is informed by the framing theory and concepts of nationalistic historiography and patriotic history .Methodologically the study is grounded in the qualitative research approach .Archival research was used to gather data from the Sunday Mails online archives .critical discourse analysis and qualitative content analysis was employed to analyse the data .The study found out that the Column Chronicles from the Second Chimurenga is propagating patriotic history as evidenced by the one sided narrative which is always in favour of the ruling party .The column does not give a voice to other parties that also played a role in the liberation of this country but are considered as hostile to ZANU PF.